PENGARUH MOTIVASI DIRI TERHADAP PROKRASTINASI AKADEMIK MAHASISWA PENDIDIKAN EKONOMI PADA MASA PANDEMI - Dicha Putri Rezkia; Almasdi Syahza; Mujiono (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article investigates the relationship between self-motivation and academic procrastination among Economic Education students at Universitas Riau during the pandemic. The study is motivated by the tendency of students to delay completing assignments due to low motivation. This quantitative descriptive study aimed to determine whether self-motivation significantly affects students’ academic procrastination. Data were collected via a questionnaire distributed through Google Forms to students from the 2018 and 2019 cohorts, with a random sampling technique applied to obtain 109 respondents. The results show that 82.6% of students had high self-motivation, while 55.9% exhibited low levels of academic procrastination. Simple linear regression analysis revealed that self-motivation had a significant effect on academic procrastination at a 5% significance level. The findings suggest that enhancing students’ self-motivation can effectively reduce academic procrastination and improve timely completion of assignments.